Uji Aktivitas Antibakteri Ekstrak Rimpang Galoba (Horstedtia Alliacea) Terhadap Bakteri Staphylococcus Aureus Dan Escherichia Colli - Maria Fenesia Fangohoi; Chikita Inaku; Abdul Suleman Wahid (STIKes Ibnu Sina Ajibarang, 2025)
Galoba rhizome (Horstedtia alliacea) is a plant that is efficacious because it contains antibacterial compounds. It contains flavanoids and triterpenoids to inhibit bacterial growth. The purpose of this study was to determine the antibacterial activity of galoba rhizome extract against Staphylococcus aureus and Escherichia coli bacteria and to determine the concentration of the extract which had the largest inhibition zone in inhibiting the growth of Staphylococcus aureus and Escherichia coli bacteria. The extraction method used is repeated maceration. Antibacterial testing using the disc diffusion method, the results of the antibacterial activity test of Staphylococcus aureus with extract concentrations of 0.5%, 1% and 1.5% each had mean ± SD values, namely: 5.9 ± 0.76.7 .63 ± 0.96, 10.16 ± 2.63 and the results of the antibacterial activity test against Escherichia coli bacteria obtained inhibition zones at concentrations of 0.5%, 1% and 1.5% each having mean ± SD values, namely: 5, 98 ± 2.10, 6.69 ± 1.22, 8.19 ± 4.48. From this study it can be concluded that Galoba rhizome extract has antibacterial activity in inhibiting the growth of Staphylococcus aureus and Escherichia coli bacteria at a concentration of 1.5% which is included in the medium category.